A double-blind controlled trial of long chain n-3 polyunsaturated fatty acids in the treatment of multiple sclerosis. Issue 1 (January 1989) - Bates, D; Cartlidge, N E; French, J M; Jackson, M J; Nightingale, S; Shaw, D A; Smith, S; Woo, E; Hawkins, S A; Millar, J H
Abstract : A trial of n-3 polyunsaturated fatty acids in the treatment of multiple sclerosis has been conducted over a 5 year period. Ambulant patients (312) with acute remitting disease were randomly allocated to treatment or placebo. Both groups were given dietary advice to increase the intake of n-6 polyunsaturated fatty acids and the treatment group in addition received capsules containing n-3 polyunsaturated fatty acids. Analysis of clinical outcome at the end of 2 years of treatment was made in terms of the duration, frequency and severity of relapses and the number of patients who had improved or remained unchanged. The results showed no significant difference at the usual 95% confidence limits but there was a trend in favour of the group treated with n-3 polyunsaturated fatty acids in all parameters examined.